The neural basis of tadpole transport in poison frogs. Issue 1907 (17th July 2019) - Fischer, Eva K.; Roland, Alexandre B.; Moskowitz, Nora A.; Tapia, Elicio E.; Summers, Kyle; Coloma, Luis A.; O'Connell, Lauren A.
Abstract : Parental care has evolved repeatedly and independently across animals. While the ecological and evolutionary significance of parental behaviour is well recognized, underlying mechanisms remain poorly understood. We took advantage of behavioural diversity across closely related species of South American poison frogs (Family Dendrobatidae) to identify neural correlates of parental behaviour shared across sexes and species. We characterized differences in neural induction, gene expression in active neurons and activity of specific neuronal types in three species with distinct care patterns: male uniparental, female uniparental and biparental. We identified the medial pallium and preoptic area as core brain regions associated with parental care, independent of sex and species. The identification of neurons active during parental care confirms a role for neuropeptides associated with care in other vertebrates as well as identifying novel candidates. Our work is the first to explore neural and molecular mechanisms of parental care in amphibians and highlights the potential for mechanistic studies in closely related but behaviourally variable species to help build a more complete understanding of how shared principles and species-specific diversity govern parental care and other social behaviour.